The mod squad - Danes, Claire, 1979-; Epps, Omar.; Ribisi, Giovanni, 1974-; Silver, Scott (Santa Monica, CA : Metro Goldwyn Mayer Pictures, Inc., 1999)
Three problem teens work undercover in the hip L.A. scene to avoid going to jail.
"907450"
"Based upon characters created by Buddy Ruskin"
Contains Widescreen and Standard versions.
Music by BC Smith ; written by Stephen Kay & Scott Silver and Kate Lanier ; directed by Scott Silver.
Starring Claire Danes, Omar Epps, Giovanni Ribisi.
Rated R.
Keywords: Feature films; Films for the hearing impaired